Analysis Of The Mental Image Of Iranian Consumers Of Foreign Luxury And Widely Used Goods From Non-Marketing Symbols Of Seven Countries Of Origin - Jafari, Mostafa; Sadeghi, Hasti; Sadeghi, Shakib (Advances in Social Sciences Research Journal, 2017)
Which country’s expensive, luxury and widely used goods should we buy? What are the non-marketing features of the country of origin as producer or exporter of commodity to Iran, and what is their importance in the mind of Iranian consumer? How are the mental images of various and different Iranian groups of seven known countries in Iran’s market, especially with the comparative perspective? This study seeks to explore the answers to these three questions.